2020
DOI: 10.1093/europace/euaa193
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of multiple fragmented QRS on cardiac events in idiopathic dilated cardiomyopathy

Abstract: Aims  To evaluate the prognostic impact of fragmented QRS (fQRS) on idiopathic dilated cardiomyopathy (DCM). Methods and results  We conducted a prospective observational study of 290 consecutive patients with DCM (left ventricular ejection fraction ≤ 40%) and narrow QRS who underwent cardiac magnetic resonance. We defined fQRS as the presence of various RSR′ patterns in ≥2 contiguous leads representing the anterior (V1–V5), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…As reported, primary prevention was independently associated with a reduced risk of shocks compared with secondary prevention, 12,19,35,37 but no difference in mortality was found. 35,37 It was also found that higher LVEDD and NT-proBNP were related to an increased risk of mortality, 19,26,32 and ACEI/ARB was related to a reduced risk of mortality, 18,20 but none of these was associated with disproportionately increased risk of sudden death. 38 Although our study showed amiodarone decreased the likelihood of death prior to shock, the mechanism was intriguing.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As reported, primary prevention was independently associated with a reduced risk of shocks compared with secondary prevention, 12,19,35,37 but no difference in mortality was found. 35,37 It was also found that higher LVEDD and NT-proBNP were related to an increased risk of mortality, 19,26,32 and ACEI/ARB was related to a reduced risk of mortality, 18,20 but none of these was associated with disproportionately increased risk of sudden death. 38 Although our study showed amiodarone decreased the likelihood of death prior to shock, the mechanism was intriguing.…”
Section: Discussionmentioning
confidence: 94%
“…Prior investigations of risk stratification for ICD recipients are either the risk of occurring ventricular arrhythmias (including VT, VF, and SCD) [26][27][28][29] or death. 6,[30][31][32] Various methods including risk score algorithm based on multivariable regression, 28 landmark analysis, 27 and random forest 26 were applied to evaluate the risk of life-threatening ventricular arrhythmias, and all showed satisfactory performance. Among models predicting survival in heart failure, the Seattle Heart Failure Model (SHFM) 31 was widely recognized.…”
Section: Discussionmentioning
confidence: 99%
“…shown that the existence of fQRS is a prognostic factor for patients with various organic heart diseases (Haraoka et al, 2010;Luo et al, 2020;Marume et al, 2021;Morita et al, 2017;Peters et al, 2008;Schuller et al, 2011). Das et al found a correlation between fQRS and the presence of a myocardial scar.…”
Section: Fragmented Qrsmentioning
confidence: 99%
“…Additionally, the myocardial scar detected by the fQRS wave is strongly associated with ventricular dysfunction and is a substrate for reentrant ventricular arrhythmia including VF. (Pietrasik & Zareba, 2012 ) Furthermore, the fQRS has been postulated to be predictive of outcomes in various organic heart diseases, such as ischemic heart disease, (Luo et al, 2020 ) dilated cardiomyopathy, (Marume et al, 2021 ) arrhythmogenic right ventricular cardiomyopathy, (Peters et al, 2008 ) sarcoidosis, (Schuller et al, 2011 ) Brugada syndrome (Morita et al, 2017 ) and acquired long QT syndrome. (Haraoka et al, 2010 ) Nevertheless, whether the fQRS is involved in the occurrence of VF in VA patients who are not considered to have organic cardiac dysfunction remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged QRS complex duration has long been a recognized risk factor for adverse cardiac events. 1,2 More recently, the socalled QRS complex fragmentation, defined by visually detected splits of QRS waves, 3,4 has also been found to predict poor outcome in both cardiac patients and other well-defined groups [5][6][7] including the general population. 4 This increased risk due to visible QRS fragmentation appears independent of the overall QRS complex duration.…”
Section: Introductionmentioning
confidence: 99%